Service based collaborative framework for smart gardening - Kavitha, V; P. Shanmugapriya, Dr; S. Aisshwaryapriya, A; Harini, M (International Journal of Engineering and Technology, 2018)
Service oriented architecture (SOA) is being an evolving technology, which allows various applications to talk with each other and share data and services through a provider, mediator and service requestor with a service description. This paper recommends a way for the development of â€œsmart gardeningâ€ using web services in combination with internet of things (IoT). This approach helps to develop, deploy, integrate and manage various services through a collaborative framework for the effective maintenance of plant growth. The usage of IoT will help people to use the sophisticated techniques to improve the maintenance. IoT is used for sensing soil moisture and nutrients, controlling water usage for plant growth and determining custom fertilizer. Further, it also aims to maintain the environmental constancy and sustainability.Â  Â
Keywords: Internet of Things; Services; Smart Gardening; SOA